Karakteristik Penderita Sindrom Koroner Akut Yang Dirawat Inap Di Bagian Kardiologi RSUD Andi Makkasau Parepare Periode 1 Januari 2015 Sampai Dengan 31 Desember 2018 - Ariedrmawan, Rachmat; Pattelongi, Ilhamjaya; Anton, Riska (Bosowa Medical Journal, 2023)
Acute coronary syndrome (ACS) is an ischemic conditions in the myocardium (heart muscle) caused by plaque in the coronary arteries and getting worst with the thrombosis process, causing obstruction that causes perfusion to the myocardium is reduced. There are several risk factors associated with acute coronary syndrome disease. These risk factors are divided into risk factors that can be changed and risk factors that cannot be changed. The aim research is Characteristics of patients with acute coronary syndrome based on (1) classification (2) age (3) gender (4) nutritional status (5) history of diabetes mellitus (6) history of hypertension (7) history of smoking habits. This study was conducted on 90 people with acute coronary syndrome who were hospitalized at the Cardiology Department of the Andi Makkasau Parepare Regional Hospital for the period January 1, 2015 to December 31, 2018. This study used a descriptive observational and analytical method with a cross sectional study design using secondary data in the form of medical records of patients with the syndrome. Acute coroners who were hospitalized at the Cardiology Section of the Andi Makkasau Parepare Regional Hospital. Data analysis was processed using SPSS software. This study shows the distribution of acute coronary syndrome patients hospitalized at RSUD Andi Makkasau Parepare from January 1, 2015 to December 31, 2018, namely: (1) The highest classification of SKA is APTS (45.6%), (2) Most are in the age group at risk (91.1%), (3) More in men (80%) than women (20%), (4) More nutritional status without risk (56.7%) than nutritional status at risk (43, 3%), (5) There was no history of diabetes mellitus (86.7%) more than there was a history of diabetes mellitus (13.3%), (6) There was more history of hypertension (57.8%) than no history of diabetes mellitus. hypertension (42.2%), (7) In this study, there was no data about the history of smoking habits in medical records as a source of data. Most patients with acute coronary syndrome in APTS, at risk age group, male, no risk nutritional status, no history of diabetes mellitus, and there is a history of hypertension